Effect of socio-economic status on the prevalence of diabetes mellitus in Indonesia - Amalia Kusumaningrum; Rico Ricardo (Intelektual Pustaka Media Utama, 2022)
The case of diabetes mellitus in Indonesia shows an increasing trend, especially in the upper socio-economic groups. This study aimed to determine the effect of socioeconomic status on the prevalence of diabetes mellitus in Indonesia using data from the Indonesia family life survey (IFLS). This study was intentionally targeted at individuals aged 15 years and over who are respondents to IFLS-5. Diabetes mellitus becomes the dependent variable, while the independent variables comprise age, gender, education, income, body mass index, and smoking behavior. Logistic regression was performed to determine the potential socio-economic factors associated with diabetes mellitus. The results reveal that socio-economic status influences the prevalence of diabetes mellitus in Indonesia. The higher the income level, the probability of diabetes mellitus increases by 0.466 percent. Meanwhile, individuals who attended university had a 2.86 percent higher probability than individuals with a primary level of education.